The Relationship between Resilience and Self Control among Rehabilitated Addicts - Nur Artricia, Mohd Jefrin Azlan; Edris, Aden (2022)
The aim of this preliminary study is to examine the relationship between resilience and selfcontrol among rehabilitated addicts via the five elements of resilience which are basics, belonging, learning, coping and core self. The number of sample was 113 rehabilitated addicts and aged between 18 - 66 years old. Resilience Assessment Tool – 43 (RAT-43) by Madihie et al. (2019) and Brief Self Control Scale (BSCS) by Tangney et al. (2004) were carried out using online Google Form. Results showed that there are significant relationships between resilience and self-control in the form of basics, belonging and core self, where the null hypothesis is being rejected. There is no significant relationship between resilience and selfcontrol in the form of learning and coping, where null hypothesis is accepted. These findings can be used to design effective counselling interventions within relapse prevention initiatives as well as to promote resilience for rehabilitated addicts. Future research could conduct study on creating a resilience model for rehabilitated addicts which can lead to new contribution to the resilience therapy research.